Challenges for Iranian Women in Daily Urban Safety - Hamedanian, Fatemeh; Ghadermazi, Sirwan (Frontiers in Sociology, 2022)
Ensuring the safety of women as a vulnerable group in urban areas is a fundamental issue and of utmost importance to issues such as violence, crime, victimization, and depression. The purpose of this study is to investigate, through qualitative analysis, the contexts, causes, and consequences of women's feelings of unsafety in urban environments. The research field of the study is the public spaces of Tehran. The subjects and their spatial and interactive dimensions were explored through in-depth individual interviews, direct observation, and participant observation, and data from this study were analyzed using grounded theory. The results show that women's feeling of not being safe in the urban space of Tehran, the capital of Iran, is the result of some influential structural factors such as “socioeconomic challenges” and “dysfunctional socialization” and some contextual factors such as “crowded places” and “showing off.” The women in the study also believe that their feelings of unsafety are reinforced by certain reasons evident in the behavior, language, and gestures of men. The feeling of unsafety among women has consequences at the micro and macro levels. Because of this feeling, women take “preventive measures” at the micro-level and at the macro-level, such feelings of unsafety lead to the spread and reinforcement of the “decay of social trust.”